Aplikasi Sistem Pendukung Keputusan Siswa Berprestasi Menggunakan Metode Topsis Berbasis Vb Net - Suci Syahfitri; Hartini Damanik; Yasmin Widiyasha; Fauziah Dea Irwanda; Monica Anastasya Putri Sinaga (PT Siantar Codes Academy Publisher, 2026)
The student achievement assessment system at the secondary school level often faces obstacles in the form of subjective, unstructured evaluation processes that require a long time when done manually. This study developed a Student Achievement Decision Support System Application using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method implemented in VB.Net. The TOPSIS method was chosen because it is capable of ranking alternatives based on their proximity to the ideal solution. This system utilizes three main criteria as the basis for assessment, namely academic achievement, activity, and discipline. All values are processed through normalization, weighting, positive and negative ideal solution calculations, to produce preference scores to determine the final student rankings. The application provides modules for student data input, value input, TOPSIS processing, and final result reports. The interface is designed to be easy to use by schools, equipped with assessment history tables and graphical visualizations of the ranking results. Test results show that the system is capable of processing data quickly, accurately, and consistently, thereby supporting an objective evaluation process. The implementation of this application is expected to help schools select high-achieving students in a more transparent, measurable, and efficient manner. With this system in place, decision-making no longer depends on subjective assessments, but rather on standardized mathematical calculations. Keywords: decision support system, TOPSIS method, VB.NET, high-achieving students